EthA/R-Independent Killing of Mycobacterium tuberculosis by Ethionamide - Ang, Michelle L. T.; Zainul Rahim, Siti Z.; de Sessions, Paola Florez; Lin, Wenwei; Koh, Vanessa; Pethe, Kevin; Hibberd, Martin L.; Alonso, Sylvie (Frontiers in Microbiology, 2017)
Ethionamide (ETH) is part of the drug arsenal available to treat multi-drug resistant tuberculosis. The current paradigm of this pro-drug activation involves the mycobacterial enzyme EthA and the transcriptional repressor, EthR. However, several lines of evidence suggest the involvement of additional players. The ethA/R locus was deleted in Mycobacterium bovis BCG and three Mycobacterium tuberculosis (MTB) strains. While complete resistance to ETH was observed with BCG ethA/R KO, drug susceptibility and dose-dependent killing were retained in the ethA/R KO MTB mutants, suggesting the existence of an alternative pathway of ETH bio-activation in MTB. We further demonstrated that this alternative pathway is EthR-independent, whereby re-introduction of ethR in ethA/R KO MTB did not lead to increased resistance to ETH. Consistently, ethA KO MTB (with intact ethR expression) displayed similar ETH susceptibility profile as their ethA/R KO counterparts. To identify the alternative ETH bio-activator, spontaneous ETH-resistant mutants were obtained from ethA/R KO MTB and whole genome sequencing identified single nucleotide polymorphisms in mshA, involved in mycothiol biosynthesis and previously linked to ETH resistance. Deletion of mshA in ethA/R KO MTB led to complete ETH resistance, supporting that the role of MshA in ETH killing is EthA/R-independent. Furthermore mshA single KO MTB displayed levels of ETH resistance similar or greater than those obtained with ethA/R KO strains, supporting that mshA is as critical as ethA/R for ETH killing efficacy.